Perancangan Sistem Pengendalian Temperatur pada Proses Pemanasan dengan Listrik Menggunakan Motor Servo sebagai Aktuator - Azhar, Azhar; Darni, Yuli; Lesmana, Donny; Irfan, Muhammad Muslim; Rianto, Yoga (Jurnal Teknologi, 2025)
The heating process is very common in many industrial fields. The heating process usually uses steam as a heating medium, especially in large-scale industries. In small-scale industries, heating with electricity is more effective and energy efficient. This study aims to examine the ability of the servo motor as an actuator to regulate the temperature in the electric heating process. The servo motor used is MG995 DC (5 Volt) with a rotation of 180O and a torque of 10 kgf/cm. The servo motor is used to rotate the potentiometer lever to regulate the power supply to the heating system. This servo motor is controlled by a PID control system with feedback input parameters in the form of DC voltage obtained from the conversion of the process temperature value (OC) using a type-K thermocouple with a sensitivity of 41V /OC. The feedback voltage from the amplified thermocouple voltage is then compared with the set point voltage (the desired process temperature value). The results of the study indicate that the servo motor can work well as an actuator to maintain the process temperature because of its accuracy in regulating the potentiometer rotation position with a PWM control range between 5% and 10%. Based on the findings of this study, it can be said that servo motors can be used as accurate actuators in regulating the supply of electrical power for electrical heating systems in industry.